DYNAMICS OF CONFLICT MANAGEMENT AND INTEGRATIVE NEGOTIATION IN MAINTAINING ORGANIZATIONAL COMMITMENT: CASE STUDY XL SMART - Novita, Sri; Siregar, Diyah Dumasari (Faculty of Economics and Business University of Lampung, 2026)
This study investigates organizational behavior dynamics during the XL Smart merger, focusing on how conflict management and integrative negotiation sustain employee commitment. Using a qualitative case study with ten key informants from strategic management to technical staffdata were gathered via in depth interviews. The findings reveal two conflict spectrums: functional (task oriented) and dysfunctional (post merger friction). Integrative negotiation, grounded in objective metrics and procedural justice, successfully converted friction into operational synergy. Crucially, transparency in negotiations bolstered affective commitment more effectively than financial compensation. By shifting focus from financial metrics to the psychological aspects of infrastructure integration, this research highlights how procedural justice stabilizes loyalty in telecommunications. Managers should prioritize reason giving and inclusive decision making to mitigate resistance. Ultimately, the Network Sharing Agreement serves as a strategic benchmark for regulators to ensure that industry consolidations balance technical efficiency with social and organizational stability.